2018
DOI: 10.2174/1566523218666180227154232
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Prospects of Non-viral Vectors in Bone Regeneration

Abstract: Thus, in this paper, we review the application and progress of non-viral gene vector therapy in bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…When developing gene therapy based on plasmid vectors for bone tissue regeneration, it is important to ensure highly efficient cell transfection to achieve a therapeutic concentration of the osteoinductor in the area of the defect. Transfecting agents that contribute to the successful delivery of plasmids into cells are able to compact plasmids and reduce their negative charge for easy transfer through the cell membrane [ 1 , 2 ]. In our previous work, we showed that when comparing two polycationic molecules, Turbofect (TF) transfected MSCs more efficiently than polyethyleneimine (PEI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When developing gene therapy based on plasmid vectors for bone tissue regeneration, it is important to ensure highly efficient cell transfection to achieve a therapeutic concentration of the osteoinductor in the area of the defect. Transfecting agents that contribute to the successful delivery of plasmids into cells are able to compact plasmids and reduce their negative charge for easy transfer through the cell membrane [ 1 , 2 ]. In our previous work, we showed that when comparing two polycationic molecules, Turbofect (TF) transfected MSCs more efficiently than polyethyleneimine (PEI).…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapy is one of the most promising approaches for bone regeneration. This method ensures local, controlled and sustained production of therapeutic proteins, simulating the natural wound-healing process [ 1 , 2 ]. Bone morphogenetic proteins (BMPs) are active participants in natural osteogenesis [ 3 , 4 ], and BMP-2, in turn, is the most effective osteoinductor that promotes the differentiation of mesenchymal stem cells (MSCs) into osteoblasts [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Viral vectors have a highly evolved mechanism for delivering DNA to cells, but could induce an effective immune response in host cells (Franceschi et al, 2004). Non-viral vector delivery is a promising gene therapy way, including cationic polymers, cationic polypeptides, and cationic liposomes (Yang et al, 2018). In tissue engineering applications, gene therapy can be combined with biomaterials to extend, persist and locally deliver the target protein in situ.…”
Section: Gene Deliverymentioning
confidence: 99%
“…15 Therefore, considerable efforts have been focused on the development of nonviral vectors with improved gene delivery efficiency. 16 Many biomaterials have been tested as nonviral vectors. For example, R 9 -LK 15 -fused cell-penetrating peptide (CPP) served as a miR-29b vector to regulate bone-marrow-derived stem cell (BMSC) differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of viral vectors has limitations, such as strong immunogenicity, high toxicity, and low loading capacity . Therefore, considerable efforts have been focused on the development of nonviral vectors with improved gene delivery efficiency …”
Section: Introductionmentioning
confidence: 99%